Use of dentifrices and mouthwashes during orthodontic treatment in the clinical management of orthodontists - Paulo André Gomes BARROS; Cláudia Batista Vieira DE LIMA; William CUSTODIO; Giovana Cherubini VENEZIAN; Silvia Amélia Scudeler VEDOVELLO; Vívian Fernandes Furletti de GÓES (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Objective: To evaluate the knowledge of orthodontic professionals regarding the prescription of dentifrices and antiseptics during orthodontic treatment. Methods: An observational and descriptive exploratory study of national scope was conducted with 440 Brazilian orthodontists, based on previous sample calculations, to evaluate the clinical practice of orthodontists in prescribing dentifrices and antiseptics. Self-managed electronic questionnaires were sent to orthodontic professionals. The data were analyzed by means of absolute and relative frequency distribution tables. Results: It was verified that the most indicated mouthwash (39.8%) was Colgate Periogard® and 421 of the participants (95.7%) know its active ingredient (chlorhexidine digluconate). Besides Colgate Periogard® antiseptic, the participants were also questioned about which active ingredient present on the following antiseptics, whose assertive answers were in the following order of %, Cepacol® (Sanofi-Aventis®) with 60.7%, Colgate Plax® (Colgate®) with 54.5% and Listerine® (Jhonson&Jhonson®) with 51.6%. As for the chlorhexidine therapeutic regime, 63.9% have stated assertively its use, being this one of 2 times a day during 7 to 10 days. The most indicated tooth was Colgate Total 12®, and 60.18% of these individuals correctly indicated its active compound. Conclusion: According to the methodology employed, it could be concluded that orthodontic professionals know and prescribe methods of chemical control to patients during orthodontic treatment and most identify the active chemical compounds present in antiseptic and tooth formulas.